미국 작물보험의 확대과정과 시사점 - 최경환 (한국농촌경제연구원, 2006)
ㅇ The main purposes of this report are to review the expansion of crop insurance programs in the U.S. since 1938 and to investigate its implications to our country which has been implementing crop insurance from 2001. Especially, this report has focused on the development progress of the mid 1990s in which many programs had been developed in the U.S. ㅇ From the U.S. experience of crop insurance, we can derive some policy implications as the following: - The U.S. government had given a greater weight on the crop insurance (including revenue insurance programs) among agricultural risk management policies supporting farmers facing several risks. - All crops were included in conducting a feasibility study before proceeding to the next process on the basis of the study. - Various insurance programs were developed and implemented for crops. The programs consisted of yield guaranteed, revenue guaranteed, and asset guaranteed ones. - From the late 1990s, many entities (especially private insurance companies) have been participating in the research and development of insurance programs under the support of the government. - The development process of crop insurance programs usually includes a feasibility study, program development, a pilot program, and evaluation and regulation. Generally, the normal process takes about 7.5～10 years. Through a step-by-step process, they aim to minimize unexpected errors. - In addition to the development of new programs, current programs have been improved through continued R & D investment. - Also, the Risk Management Agency (RMA), which is authorized to manage federal crop insurance, has been strengthening risk management education to help farmers deal with various risks during farming. - Finally, the government has been substantially intervening in the maintenance and expansion of crop insurance. It has subsidized farmers' premiums, assumed reinsurance, supported operating costs for private insurance companies, and reimbursed R & D expenses. Researcher : Kyeong-Hwan Choi E-mail Address : kyeong@krei.re.kr